Update on the pathogenesis and genetics of Paget’s disease of bone - Gennari, Luigi; Rendina, Domenico; Merlotti, Daniela; Cavati, Guido; Mingiano, Christian; Cosso, Roberta; Materozzi, Maria; Pirrotta, Filippo; Abate, Veronica; Calabrese, Marco; Falchetti, Alberto (Frontiers in Cell and Developmental Biology, 2022)
Studies over the past two decades have led to major advances in the pathogenesis of Paget’s disease of bone (PDB) and particularly on the role of genetic factors. Germline mutations of different genes have been identified, as a possible cause of this disorder, and most of the underlying pathways are implicated in the regulation of osteoclast differentiation and function, whereas other are involved in cell autophagy mechanisms. In particular, about 30 different germline mutations of the Sequestosome 1 gene (SQSTM1) have been described in a significant proportion of familial and sporadic PDB cases. The majority of SQSTM1 mutations affect the ubiquitin-binding domain of the protein and are associated to a more severe clinical expression of the disease. Also, germline mutations in the ZNF687 and PFN1 genes have been associated to severe, early onset, polyostotic PDB with increased susceptibly to neoplastic degeneration, particularly giant cell tumor. Mutations in the VCP (Valosin Containing Protein) gene cause the autosomal dominant syndrome “Inclusion Body Myopathy, PDB, Fronto-temporal Dementia,” characterized by pagetic manifestations, associated with myopathy, amyotrophic lateral sclerosis and fronto-temporal dementia. Moreover, germline mutations in the TNFRSF11A gene, which encodes for RANK, were associated with rare syndromes showing some histopathological, radiological, and clinical overlap with PDB and in two cases of early onset PDB-like disease. Likewise, genome wide association studies performed in unrelated PDB cases identified other potential predisposition genes and/or susceptibility loci. Thus, it is likely that polygenic factors are involved in the PDB pathogenesis in many individuals and that modifying genes may contribute in refining the clinical phenotype. Moreover, the contribution of somatic mutations of SQSTM1 gene and/or epigenetic mechanisms in the pathogenesis of skeletal pagetic abnormalities and eventually neoplastic degeneration, cannot be excluded. Indeed, clinical and experimental observations indicate that genetic susceptibility might not be a sufficient condition for the clinical development of PDB without the concomitant intervention of viral infection, in primis paramixoviruses, and/or other environmental factors (e.g., pesticides, heavy metals or tobacco exposure), at least in a subset of cases. This review summarizes the most important advances that have been made in the field of cellular and molecular biology PDB over the past decades.